2022
DOI: 10.1038/s41598-022-13058-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review: normative reference values of the median nerve cross-sectional area using ultrasonography in healthy individuals

Abstract: Median nerve cross-sectional area (CSA) was used for screening and diagnosis of neuropathy, but few studies have suggested reference range. Hence, this systematic review was performed to evaluate a normative values of median nerve CSA at various landmarks of upper limb based on ultrasonography. PubMed and Web of science were used to search relevant articles from 2000 to 2020. Forty-one eligible articles (2504 nerves) were included to access median nerve CSA at different landmarks (mid-arm, elbow, mid-forearm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…US on median nerve CSA have been compared between healthy controls and patients with peripheral neuropathy. A systematic review reported a mean normative reference value of 8.74 mm 2 for median nerve CSA at the CT entrance, which is approximately the same site as the wrist crease assessed in the present study (n = 1863) [ 29 ]. Furthermore, the systematic review found no correlation between age or sex and reported a value for median nerve CSA at the CT inlet that appeared to be similar between each region.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…US on median nerve CSA have been compared between healthy controls and patients with peripheral neuropathy. A systematic review reported a mean normative reference value of 8.74 mm 2 for median nerve CSA at the CT entrance, which is approximately the same site as the wrist crease assessed in the present study (n = 1863) [ 29 ]. Furthermore, the systematic review found no correlation between age or sex and reported a value for median nerve CSA at the CT inlet that appeared to be similar between each region.…”
Section: Discussionmentioning
confidence: 80%
“…On the other hand, individual and site-specific differences in median nerve CSA were not small. Among studies measuring normal median nerve CSA at the CT inlet level, individual values widely ranged between 7 and 10 mm 2 (lower and upper bounds of 95% CI, respectively) [ 29 ]. Nakamichi et al measured the median nerve CSA of CTS patients at three different levels (the distal edge of the flexor retinaculum, the hook of the hamate, and at the wrist crease) and suggested that the median nerve had an hourglass-like shape [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the largest diameter was observed at CTO. Evidently, MNCSA has its largest diameter at the level of the hamate bone (CTO) 6 …”
Section: Discussionmentioning
confidence: 99%
“…In the most recent review, the mean MNCSA was 8.81 mm 2 at mid-arm, 8.57 mm 2 at the elbow, 7.07 mm 2 at midforearm, 8.74 mm 2 at CTI, and 9.02 mm 2 at CTO. 6 Another study reported normal MNCSAs to be 8.2 mm 2 at the level of the radiocarpal joint, 8.3 mm 2 at CTI, and 8.1 mm 2 at CTO. 7 A handful of studies have provided reference values for MNCSA in certain sample populations.…”
Section: Introductionmentioning
confidence: 96%
“…Those parameters were not investigated and could have influence on MN thickness. 22 In addition, US is an operator-dependent test, and appropriate experience is required to ensure reproducibility. There were no data collected on interobserver or intraobserver variability.…”
Section: Case Reportmentioning
confidence: 99%